Considerations about theory, poetics and analysis of ancient music (Orfeu, 2020)
Music theory, as a category of thought about music, historically constitutes itself as a representative concept of the ways considered valid to know music, directly conditioned by the culture that produces it. In the context of ancient music, this concept was associated with others, such as poetics and musical practice, which defined, according to specific purposes, the possibilities of making and understanding music. Starting from a hermeneutic perspective, in the manner of a case study, this article presents an investigation about the concept of music theory in the specific context of 17th century Lutheran music and assesses its relationship with the concepts of poetics and music analysis, within the framework of Joachim Burmeister’s treatise entitled Musica Poetica (1606).
Keywords: Music Theory; Musical Poetics; Music Analysis; Joachim Burmeister